2017
DOI: 10.3847/1538-4357/aa8598
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon and Nitrogen Abundance Ratio in the Broad Line Region of Tidal Disruption Events

Abstract: The rest-frame UV spectra of three recent tidal disruption events (TDEs), ASASSN-14li, PTF15af and iPTF16fnl display strong nitrogen emission lines but weak or undetectable carbon lines. In these three objects, the upper limits of the C iii] λ1908/N iii] λ1750 ratio are about two orders of magnitude lower than those of quasars, suggesting a high abundance ratio of [N/C]. With detailed photoionization simulations, we demonstrate that C 2+ and N 2+ are formed in the same zone, so the Ciii]/N iii] ratio depends o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 59 publications
1
40
0
1
Order By: Relevance
“…Furthermore, C iii] λ1908, having a similar ionization potential to that of N iii] (47.9 eV vs. 47.5 eV), is also absent. Since the ratio C iii]/N iii] has only a moderate dependence on the physical conditions of the gas (under local thermodynamic equilibrium conditions), the lack of C in the spectra of TDEs has been attributed to the unusually high abundance ratio of N to C in the debris of the disrupted star (Kochanek 2016a;Yang et al 2017).…”
Section: Broad Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, C iii] λ1908, having a similar ionization potential to that of N iii] (47.9 eV vs. 47.5 eV), is also absent. Since the ratio C iii]/N iii] has only a moderate dependence on the physical conditions of the gas (under local thermodynamic equilibrium conditions), the lack of C in the spectra of TDEs has been attributed to the unusually high abundance ratio of N to C in the debris of the disrupted star (Kochanek 2016a;Yang et al 2017).…”
Section: Broad Linesmentioning
confidence: 99%
“…While the semiforbidden N iii] lines are clearly detected with broad velocity spread, the C iii] is lacking in all three TDEs having FUV spectra. The origin for this discrepancy has been associated with the nitrogen-enhanced composition of the stellar debris for super-solar-mass stars (Kochanek 2016b;Yang et al 2017). The carbonnitrogen-oxygen cycle would have substantially altered the star's composition with enhanced nitrogen at the expenses of carbon, translated into the observed line ratios.…”
Section: Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the prominent N III] λ1750 relative to C III] λ1909 in TDEs may imply abundance anomalies due to CNO cycle in the pre-disrupted star (Cenko et al 2016;Kochanek 2016). Simulations have shown that the anomalous abundance features should be present after the time of peak fallback rate (t peak ) and are more significant in higher mass stars (Kochanek 2016;Yang et al 2017;Gallegos-Garcia et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of even a single star could be enough to temporarily pollute the broad-line region (BLR) gas, assuming the BLR gas mass is on the order of 10 −3 M ⊙ 1 (Peterson 1997). Although significant differences exist between the rest-frame UV spec-tra of low-redshift TDEs and high-redshift N-rich quasars, unusually strong nitrogen emission is seen in all of the three optical TDEs that have UV spectra in low-redshift galaxies (Cenko et al 2016;Yang et al 2017;Brown et al 2018).…”
Section: Introductionmentioning
confidence: 99%